Synthesis of lead molybdate and lead tungstate via microwave irradiation method - Anukorn Phuruangrat (2018)
Nanocrystallines lead molybdate and lead tungstate were successfully prepared by microwave irradiation method. The products were characterized by XRD, Raman spectroscopy, TEM and luminescence spectroscopy. The phase of products were detected by XRD and was in accordance with that of the XRD simulation using CaRIne Version 3.1 program. TEM showed the particle sizes of 15-50 nm for PbMoO4and 12-32 nm for PbWO4. Their photoluminescent spectra were decomposed to four individual Gaussian components in blue and green wavelength range for PbMoO4and three individual Gaussian components in blue wavelength range for PbWO4. These photoluminescent features could be interpreted by Jahn-Teller splitting effect on [MO4]2-(M{double bond, long}Ma and W) tetrahedrons. © 2009 Elsevier B.V. All rights reserved.